The formative use of summative assessments at the U.S. Army Command and General Staff School: a qualitative case study - Burket, Dennis S. (Kansas State University, 2016)
This qualitative case study sought to understand in what formative ways instructors in one teaching department of the U.S. Army Command and General Staff College (CGSC) used common summative assessments and what similar practices instructors used as a result of common summative assessments. This research analyzed data from semi-structured interviews with purposefully selected participants, instructors in the Department of Army Tactics at CGSC, a representative mixture of civilian and active duty. This research confirmed that the formative use of summative assessments was typical among Department of Army tactics instructors and that continued or expanded formative use of summative assessments will increase student learning. Because so much of assessment is context dependent, this research will add to the body of knowledge in a particular area that the current literature did not fully address; the formative use of common summative assessments in higher education. Four conclusions were drawn from analysis of this research. First, the formative use of common summative assessments, especially feedback given to students, was typical of the Department of Army Tactics instructor, essentially a normal part of the assessment process. Second, DTAC instructors did not have a common understanding of the difference between summative and formative assessment, how they used the information gathered was more important than what the instrument was labeled. Third, “teaching to the curriculum” instead of “teaching the test” was typical in DTAC, an indication that the instructors saw their role beyond just preparing students for upcoming assessments. Fourth, the stratification of students during the grading process was typical, with the unintended consequence of students not being judged on quality of work alone.
Keywords: Formative use of summative assessment; Qualitative; Case Study